Kitten Crowed - "Daniel, Lucy" (Hodder Children's Books: London, 1996)
Mandy, who loves solving her friends' pet problems, promises to help Sarah find homes for her cat's six baby kittens before she moves house. Just as Mandy thinks she has found the perfect place - a local old people's home whose residents need cheering up - the kittens go missing
Keywords: Cats Fiction